2009
DOI: 10.1029/2009gl038252
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous biogeochemical conditions in the northern South China Sea during the El‐Niño events between 1997 and 2003

Abstract: [1] Anomalous biogeochemical conditions were observed at the SouthEast Asian Time-series Study (SEATS) station in the northern South China Sea (SCS) during the 1997-98 and 2002-03 El Niño events. The time-series records showed decreases of monthly mean sea surface chlorophylla (S-chl) (and integrated primary production, IPP) by 42% (and 42%) and 13% (and 10%), respectively, below the climatological mean in the winter months (DJF) of the two events. The negative anomalies in S-chl and IPP corresponded to elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…However, the northeast monsoon alone does not fully elucidate the strong inter-annual variations. For instance, the winter wind speed in El Niño years was 11-20% lower than the climatological mean between 1997 and 2003 [23]. Conversely, the peak value of the mass fluxes in December 2008 was almost three times that in January 2016 (Figure 3).…”
Section: Intrusion Of Wps Seawater Reduces Export Production and Massmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the northeast monsoon alone does not fully elucidate the strong inter-annual variations. For instance, the winter wind speed in El Niño years was 11-20% lower than the climatological mean between 1997 and 2003 [23]. Conversely, the peak value of the mass fluxes in December 2008 was almost three times that in January 2016 (Figure 3).…”
Section: Intrusion Of Wps Seawater Reduces Export Production and Massmentioning
confidence: 93%
“…The winter bloom is widely recognized to be triggered by the increased nutrient inventory under the influence of the strong northeast monsoon [11,[23][24][25]. However, the northeast monsoon alone does not fully elucidate the strong inter-annual variations.…”
Section: Intrusion Of Wps Seawater Reduces Export Production and Massmentioning
confidence: 99%
“…However, Kuroshio intrusion induced mesoscale eddies in that area, which caused the Δ 14 C in Currimao to be the lowest among the five studied locations. According to Tseng et al (2009), weakening of the monsoon decreases the extent of vertical mixing in the northern SCS. The East Asian winter monsoon velocity decreased from the 1970s to the 1980s (Song et al 2012); thus, the area of mesoscale eddies decreased in size after 1976.…”
Section: Winters After the Mid-1980smentioning
confidence: 99%
“…Among them, the RMSE and MAPD of MLD mdg were the lowest and came close to those of MLD T5 , MLD T10 , and MLD θG . In previous studies, MLG T8 (Qu et al 2007), MLD θG (Qu 2001;Ge et al 2003;Hao et al 2012), MLD σG5 (Tseng et al 2007), and MLD σG10 (Tseng et al 2005(Tseng et al , 2009Wong et al 2007a, b) have been used for estimating MLD in the SCS. Only the results in the first two sets of studies may be readily compared to each other even after a constant offset has been applied.…”
Section: Classical Type Upper Water Hydrographic Structurementioning
confidence: 99%
“…As a result, MLD generally tends to decrease with decreasing latitude, and, the seasonal variations in MLD in the tropical waters tend to be smaller (Monterey and Levitus 1997;Montégut et al 2004). As a part of several studies for diverse purposes, the MLD in the tropical northern South China Sea (SCS) has been estimated by various investigators using a variety of different methods: a FTD method with a drop in θ of 0.8°C relative to that at 10 m (Qu et al 2007); a FTG method at a temperature gradient of 0.05°C m -1 (Qu 2001;Ge et al 2003;Hao et al 2012); a FDG method at density gradients of 0.05 (Tseng et al 2007) or 0.1 σ θ unit/m (Tseng et al 2005(Tseng et al , 2009Wong et al 2007b). Wong et al (2007b) reported that, unlike what is expected in tropical waters, the MLD in the northern SCS varies over a relatively wide range seasonally, from 20 m in the summer to 90 m in the winter.…”
Section: Introductionmentioning
confidence: 99%